Clinical Spectrum, Etiology And Outcomes Of Pediatric Pancreatitis: A Tertiary Care Experience - Yatoo, Tanveer Ahmad; Akhter, Zahidah; Javid, Waseem (Journal of Neonatal Surgery, 2025)
Background: Pancreatitis in children is an increasingly recognized condition with diverse etiologies and clinical presentations. This study aims to evaluate the spectrum of pediatric pancreatitis in a cohort of 30 children. Methods: A prospective analysis was conducted on 30 pediatric patients diagnosed with pancreatitis in departments of Gastroenterology and General surgery, GMC Srinagar Kashmir from Dec 2018 to Dec 2023. Data on demographics, clinical presentation, laboratory findings, imaging characteristics, etiology, management, and outcomes were collected and analyzed. Results: The median age of the patients was 12 years, with a male-to-female ratio of 1.5:1. The most common presenting symptoms were abdominal pain (90%), vomiting (72%), and fever (60%). Etiologies included idiopathic (33%), biliary (20%), trauma-related (13%) metabolic causes (13%) and medication-induced (6%).Serum amylase and lipase were elevated in 73% and 83% of cases. Imaging revealed pancreatic enlargement in 66% and necrotizing pancreatitis in 33.33% of cases. Management strategies varied, including supportive care (65%), nutritional interventions (13%), and specific etiological treatments (36.66%). The overall recovery rate was 100%. Conclusion: Pediatric pancreatitis presents with a wide clinical spectrum, requiring a thorough diagnostic approach to determine the underlying etiology. Early recognition and appropriate management can improve outcomes. Further studies with larger cohorts are needed to enhance understanding and optimize treatment protocols.